Acquisition and analysis of 3D mandibular movement using a device based on electromagnetic sensors and a neural network - Isa C. T. Santos (2009)
In dental medicine, the study of mandibular movement has an important role in oral rehabilitation as it allows diagnosis of pathologies in the temporomandibular joint and the definition of adequate treatment plans. In this paper, a new device specially developed for the acquisition and analysis of 3D mandibular movement is presented. A facial arc is adopted as its main support structure and electromagnetic sensors are employed to acquire the mandibular movement. A neural network is used to transform the electrical signals output by the sensors into 3D Cartesian coordinates. A custom-made computer application is developed to display and analyse the movement acquired. The device is shown to be easy to use, comfortable for patients and capable of being produced at an affordable price.